History of the Decline and Fall of the Roman Empire $1 (BVolume 2s - Gibbon, Edward, 1737-1794; Milman, Henry Hart, 1791-1868 (Salt Lake City, UT : Project Gutenberg, 2008)
"History of the Decline and Fall of the Roman Empire $1 (BVolume 2" by Edward Gibbon is a historical work published in 1781. This volume continues Gibbon's monumental chronicle of Rome's transformation from imperial peak to collapse. Spanning fifteen centuries, the work examines Christianity's emergence as state religion, barbarian invasions, and the gradual loss of civic virtue that undermined the empire. Written with detached yet critical prose, Gibbon's controversial thesis challenged conventional views of Christianity's role in Rome's fate, sparking debates that continue among scholars today. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_History_of_the_Decline_and_Fall_of_the_Roman_Empire
HTML
Release date is 2008-06-07
Produced by David Reed, Dale R. Fredrickson and David Widger
Keywords: Rome -- History -- Empire, 30 B.C.-476 A.D.; Byzantine Empire -- History -- To 527